2009
DOI: 10.1098/rstb.2009.0076
|View full text |Cite
|
Sign up to set email alerts
|

The potency of different serotonergic agonists in counteracting opioid evoked cardiorespiratory disturbances

Abstract: Serotonin receptor (5-HTR) agonists that target 5-HT 4(a) R and 5-HT 1A R can reverse m-opioid receptor (m-OR)-evoked respiratory depression. Here, we have tested whether such rescuing by serotonin agonists also applies to the cardiovascular system. In working heart-brainstem preparations in situ, we have recorded phrenic nerve activity, thoracic sympathetic chain activity (SCA), vascular resistance and heart rate (HR) and in conscious rats, diaphragmatic electromyogram, arterial blood pressure (BP) and HR via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
3
29
0
2
Order By: Relevance
“…This inhibitory effect has been demonstrated in late-E neurons of anesthetized cats (12) and most likely contributes to the effects seen with 8-OH-DPAT. More recently it has been shown that the glycinergic inhibitor strychnine abolishes the effects of 8-OH-DPAT in rats studied in situ (14). Thus glycine-mediated inhibition may also add to the correction of respiratory disturbances seen with the serotonin 1a agonist.…”
Section: Mechanism Of Serotonin 1a Agonist Induced Inhibition Of Expimentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibitory effect has been demonstrated in late-E neurons of anesthetized cats (12) and most likely contributes to the effects seen with 8-OH-DPAT. More recently it has been shown that the glycinergic inhibitor strychnine abolishes the effects of 8-OH-DPAT in rats studied in situ (14). Thus glycine-mediated inhibition may also add to the correction of respiratory disturbances seen with the serotonin 1a agonist.…”
Section: Mechanism Of Serotonin 1a Agonist Induced Inhibition Of Expimentioning
confidence: 99%
“…Because serotonin 1a receptor agonists have been shown to both inhibit expiratory neurons (12) and reinstate breathing after opioid-induced central apneas (13,14), we tested whether 8-hydroxy-dipropyl-aminotetralin (8-OH-DPAT) (a serotonin 1a receptor agonist) could depress the respiratory apneas in Mecp2 heterozygote mice. Our findings reveal that both treatments significantly reduced apneas and periodic breathing in Mecp2-deficient mice and restored regularity to their cycle intervals.…”
mentioning
confidence: 99%
“…The noradrenergic A7 cell group also overlaps with the KF. In addition to GABA, glycine, and noradrenalin receptors, various glutamate (AMPA/kainic acid, NMDA, and metabotropic receptors (59, 149152) and cholinergic and serotonergic (5-HT) receptors are expressed in the PB and KF nuclei (103, 165, 244). Moreover, large subset of neuropeptide transmitters such as neurotensin, cholecystokinin, substance P, somatostatin, and calcitonin gene-related peptide and their associated receptors are also expressed (324327).…”
Section: The Parabrachial Complex and Kölliker-fuse Nuclei Of The Dormentioning
confidence: 99%
“…Recent evidence provided by Diethelm Richter’s group suggest that 5-HT 4 R or 5-HT 1A R mediated recovery of μ-opioid receptor evoked respiratory depression or even total arrest (Manzke et al 2003, 2009). The use of a 5-HT 1A R agonist has been shown to evoke breathing recovery following opioid induced respiratory depression in awake rodents (Dutschmann et al, 2009). However it needs to be mentioned that preliminary test in humans failed to produce similar beneficial effect on opioid evoked respiratory depression (Lötsch et al, 2005; Oertel et al, 2007).…”
Section: Therapeutic Use Of Serotonergic Drugs In Central Respiratmentioning
confidence: 99%